Selebrasi dalam Perspektif Hadis : Studi Hadis Tematik - Mutiara Irawati; Muhammad Alif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Celebration is part of human emotional expression that is often carried out in various forms, ranging from personal celebrations to collective moments such as the success of a sports team or major religious holidays.This article aims to examine the phenomenon of celebration from the perspective of the hadith of Prophet Muhammad SAW, by reviewing several narrations related to expressions of joy, forms of celebrations, and the Shari'ah limits in their implementation.This study uses a qualitative-descriptive method with a thematic approach to relevant hadiths, both from the nine canonical collections and the commentary books.The study results show that Islam does not prohibit forms of celebration as long as they do not contain elements of sin, violate Sharia norms, or imitate traditions that contradict Islamic teachings.Hadiths show that the Prophet Muhammad (peace be upon him) himself did not deny expressions of joy as long as they were done within reasonable and meaningful limits.Therefore, celebrations in Islam are considered a means of expressing legitimate gratitude and happiness, as long as they are conducted in accordance with true Islamic values.